Search 75,604 tutors
0 0

## Need to Find X

y = (x * .4175) + x
where y = 874.90

Hi Jessica,

Here you go ~

y = (x * .4175) + x

Substituting y and rewriting -

874.90 = .4175x + x

874.90 = .4175x + 1x

874.90 = 1.4175x

Now, let's rewrite the equation again and solve for x -

x = 874.90/1.4175

x = 617.21

I hope this helps!

Rashonda J.
Rewrite the equation as y = x*(0.4175+1)
y = 1.4175*x
x = y/1.4175
x = 874.9/1.4175 = 617.2134
y = [x*(0.4175)] = x

y = 874.90 = x*(1 + 0.4175) = 1.4175*x

∴ x = 874.9/1.4175 = 617.2
Hi Jessica,

You must 1st substitute the value of y into the equation.

874.90 = (x*.4175) + x

874.90 = .4175x + x

874.90 = 1.4175x

Now divide each side of the equation by 1.4175.

874.90/1.4175 = 1.4175x/1.4175

874.90/1.4175 = x

x = 617.213404
Hi Jessica,

For this algebra equation, you'll want to use substitution. Take the value of y (874.90) and plug it into your equation.

874.90 = (x * 0.4175) + x

Now let's combine the terms on the right side of the equation.

874.90 = 1.4175x                            (because 1x + 0.4175x = 1.4175x)

Next, divide both sides by 1.4175

874.90/1.4175 = x

So, x is approximately 617.21

(Note, it's always a good idea to check your answer. To do that, plug our answer for x back into our original equation and see if y turns out to be 874.90.)
D'oh!, of course zeroth, make sure you copy down the problem right :-)

First, Combine like terms:

y = (x * .4175) + x = 1.4175 * x

y = 1.4175 * x

Second, solve for x (get x by itself):

Multiply both sides by (1/1.4175)

(1/1.4175) * y = (1/1.4175) * 1.4175 * x

y / 1.4175 = (1) * x

x = y / 1.4175

Finally, substitute in your value for y:

x = 874.90/1.4175 = 617.2134ish
(or 8749000 / 14175 = 349960 / 567 if that's how you roll)